SELECTED ASPECTS OF THE IMPLEMENTATION OF ACTIVE MARKETING CAMPAIGN TO RAISE AWARENESS AND PROMOTE PUBLIC TRANSPORT SERVICES IN RURAL AREAS - Katarzyna NOSAL; Urszula DUDA (Scientific Journal of Silesian University of Technology. Series Transport)
The article presents selected aspects of the implementation of the EU’s SmartMove project, which aims to promote feeder public transport systems in rural areas through the implementation of an active marketing campaign (AMC). Campaigns of this type are connected with providing general and personalized information concerning the functioning of public transport services. In the article, characteristics of one of the implementation areas of the project are presented, namely, the Liszki district near Cracow. Transport services were also evaluated. In addition, selected results are presented from a survey that was conducted among residents of the area from the point of view of the implementation of the AMC. The results concerned data about the means of transport that were currently used for travelling, the knowledge of bus services, the reasons for their use and the factors that might encourage residents to use public transport